Records on italian species of Chionea s.l. (Diptera Limnobiidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
We have found in High Valtellina Valley the presence of three species of Diptera Limnobiidae; belonging to genus Chionea Dalm. and Niphadobata Enderlein.That is, in particular, C. minuta Tahvonen (first discovery for Italy), N. alpina (Bezzi) and N. lutescens (Lundstrom). We have found some specimens of this last one only supplied with antenna 5-articulated; therefore we have thought of calling it "stelviana ssp. n.". After a short examination of the morphological characters of the three species, we have examined the biology of these Diptera living on the snow.